La presencia de lo extranjero en las novedades bibliográficas de La Ilustración Española y Americana (1869-1905) - Anna-Maria Corredor Plaja (Cahiers de Civilisation Espagnole Contemporaine)
There is no doubt that La Ilustración Española y Americana (LIEA), magazine that includes approximately the last third of the 19th century and the first twenty years of the 20th century (1869-1921), had a relevant role from the point of view of the diffusion of the foreign culture in our country, as it has been proved by the numerous works that have been published in this matter. This work is based on the study of a part of the content of one of its sections, the one that gives account of the bibliographical innovations come to the magazine office. Concretely we have centred on the publications that take the Portuguese language or the culture as a common denominator and that turn out to be announced in the above mentioned section during the years 1869-1905.